Physics in Badminton: How Prospective Coaches Perceive and Apply Torque Concepts - Tian Kurniawan; Nuzulira Janeusse Fratiwi; Nurdini Nurdini; Herdiansyah Agus; Nur Habib Muhammad Iqbal; Reza Ruhbani Amarulloh; Achmad Samsudin (CV. FOUNDAE, 2025)
Background: Training methodologies in badminton often focus on technique and endurance, yet the integration of scientific principles, such as torque, remains underutilized. As a critical factor influencing shot power, speed, and accuracy, a deeper understanding of torque can optimize training effectiveness and systematically enhance athlete performance.Aims: This research aims to analyze prospective badminton coaches’ understanding and application of physics concepts, particularly torque, in training methodologies.Methods: This research employed the qualitative descriptive method involving 24 prospective badminton coaches (17 males and 7 females, aged 18-22) in Bandung, Indonesia. A survey was conducted to assess their understanding of physics and its application in training. Data collected through the questionnaire was analyzed using NVivo software, which facilitated thematic analysis and coding of qualitative responses.Results: The findings indicate that, while most of the respondents are familiar with physics terms, only a few recognize torque as a relevant concept in the badminton context. A deeper understanding of torque can help coaches optimize playing techniques by improving racket rotation efficiency, thereby enhancing hitting power with minimal energy expenditure.Conclusion: This research demonstrates that integrating physics concepts, particularly torque on the racket, into badminton training provides a valuable perspective for improving training quality. The findings suggest that badminton coach training programs should integrate physics concepts to enhance training effectiveness and efficiency while systematically improving athlete performance based on scientific evidence.